Coxsackievirus-induced miR-21 disrupts cardiomyocyte interactions via the downregulation of intercalated disk components. - Xin Ye; Huifang Mary Zhang; Ye Qiu; Paul J Hanson; Maged Gomaa Hemida; Wei Wei; Pamela A Hoodless; Fanny Chu; Decheng Yang (PLoS Pathogens)
Intercalated disks (ICDs) are substantial connections maintaining cardiac structures and mediating signal communications among cardiomyocytes. Deficiency in ICD components such as desmosomes, fascia adherens and gap junctions leads to heart dysfunction. Coxsackievirus B3 (CVB3) infection induces cardiac failure but its pathogenic effect on ICDs is unclear. Here we show that CVB3-induced miR-21 expression affects ICD structure, i.e., upregulated miR-21 targets YOD1, a deubiquitinating enzyme, to enhance the K48-linked ubiquitination and degradation of desmin, resulting in disruption of desmosomes. Inhibition of miR-21 preserves desmin during CVB3 infection. Treatment with proteasome inhibitors blocks miR-21-mediated desmin degradation. Transfection of miR-21 or knockdown of YOD1 triggers co-localization of desmin with proteasomes. We also identified K108 and K406 as important sites for desmin ubiquintination and degradation. In addition, miR-21 directly targets vinculin, leading to disturbed fascia adherens evidenced by the suppression and disorientation of pan-cadherin and α-E-catenin proteins, two fascia adherens-components. Our findings suggest a new mechanism of miR-21 in modulating cell-cell interactions of cardiomyocytes during CVB3 infection.